2019
DOI: 10.1002/ejoc.201901286
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Triaryl‐Substituted Chromans with Multiple Stereogenic Centers by [4+2] Cycloaddition Reaction

Abstract: Asymmetric synthesis of triaryl-substituted chromans with multiple adjacent stereogenic centers is described here.[4+2] formal oxa-Diels-Alder cycloaddition of 1-styrylnaphthols and in-situ-generated o-quinone metheides could proceed smoothly in the presence of H 8 -BINOL-type chiral imidodiphos- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 60 publications
0
9
0
1
Order By: Relevance
“…Zhang et al demonstrated the synthesis of trisubstituted chromans 122 with multiple stereocenters (Scheme 42). [ 177 ] This process made use of 1‐styrylnaphthols 120 and ortho‐ hydroxybenzyl alcohols 33 . The most reactive ortho‐ QM intermediates were formed in‐situ from ortho ‐hydroxybenzyl alcohols 33 , which then via a formal [4 + 2] cycloaddition oxa‐Diels–Alder reaction with diene derivatives afforded the cyclic ether products.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al demonstrated the synthesis of trisubstituted chromans 122 with multiple stereocenters (Scheme 42). [ 177 ] This process made use of 1‐styrylnaphthols 120 and ortho‐ hydroxybenzyl alcohols 33 . The most reactive ortho‐ QM intermediates were formed in‐situ from ortho ‐hydroxybenzyl alcohols 33 , which then via a formal [4 + 2] cycloaddition oxa‐Diels–Alder reaction with diene derivatives afforded the cyclic ether products.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this reaction system involving o-hydroxynaphthalene needed to continue to optimize the reaction conditions. Subsequently, other groups including Zhang [20] (Scheme 8a), Yuan and You [21] (Scheme 8b), Deng and Shao [22] (Schemes 8c and 8d) independently published beautiful works about the same cycloaddition process of o-hydroxynaphthalene 34 by using different CPA catalysts, again forming a wide range of polysubstituted chromans (35,40) with high level of stereoselectivities. Notably, the lessexplored ortho-alkenyl 1-naphthols were also compatible in this methodology to deliver trans-trans chiral trisubstituted chromans 40.…”
Section: Chiral Phosphoric Acidmentioning
confidence: 99%
“…Diversely substituted chromans are readily available through [4 þ 2] regioselective cycloaddition reactions using various o-quinone methides as starting materials: i) formed from 2-[hydroxy(aryl)methyl]phenols with silver oxide and further reaction with terminal alkenes in ethyl acetate promoted by a thioxanthylium photoredox catalyst under green light LED irradiation (19JOC10669); ii) reaction of salicylaldehydes with terminal alkenes or acetophenones (19JOC13858) or with arylacetaldehyde dimethyl acetals (Scheme 28) (19SL189), TfOH, and trimethyl orthoformate in dry toluene; iii) formed in situ from 2-[hydroxy(aryl)methyl]phenols with 1-styrylnaphth-1-ols in the presence of H 8 -BINOL-type chiral imidodiphosphoric acids as catalyst and molecular sieves in toluene (19EJO7264); iv) formed in situ from 2-[hydroxy(alkyl/aryl)methyl]phenols with methyl (S,E)-3-[dimethyl(phenyl)silyl]hex-4-enoate mediated by anhydrous iron(III) chloride in the presence of 2,6-lutidine in chloroform (19OL32); and v) formed from chemoenzymatic transformation of o-cresols into benzylic alcohols, followed by the loss of water and subsequent reaction with terminal alkenes (19JA20269).…”
Section: Scheme 25mentioning
confidence: 99%